STUDI ANALISIS DATA DIFRAKSI SINAR-X PADA MATERIAL ZIRCON PASIR ALAM MELALUI METODE RIETVELD - Sefrilita Risqi Adikaning Rani (JFT : Jurnal Fisika dan Terapannya, 2022)
ZrSiO4 (zircon) material derived from natural sand has been successfully synthesized to produce single crystals. Structural analysis and phase change were studied by X-Ray diffraction. Rietveld analysis was carried out as a method of analyzing X-Ray Diffraction data. Zircon with a tetragonal crystal structure has been successfully synthesized to produce single crystals of ZrSiO4 with space group I41/amd. The results of the Rietveld analysis of single crystal ZrSiO4 samples with a tetragonal structure obtained lattice parameters a= 6.602727 (323) c= 5.978810 (317) with a crystal size distribution of 527.033 (0) nm and macrostrains of 0.001x10-4.